Algorithm Visualization in Teaching Spatial Data Algorithms - Nikander, J.; Helminen, J. (2007 11th International Conference Information Visualization (IV '07), 2007)
Algorithm visualization is a widely-used tool for teaching data structures and algorithms. Spatial data algorithms are algorithms that are designed to process multidimensional data. This work introduces a spatial data extension to the successful TRAKLA2 learning environment, which includes automatically assessed visual algorithm simulation exercises. First impressions on using the visualizations in teaching are also described.